Thinning experiment in a Scots pine (Pinus sylvestris L.) natural regeneration stand in the Central range - Montero González, G.; del Río Gaztelurrutia, M.; Ortega Muela, C. (Forest Systems, 2000)
A thinning experience was carried out in a Scots pine natural regeneration stand in the Central range with a site index of 23, according to the quality curves given by Rojo and Montero (1996). The age of the stand at the beginning of the experience (1971) was 35 years, and 60 years at the last inventory (1996). The statistical design of the trial was a randomised complete block with four treatments and three blocks. One treatment was a control or unthinned (A), and the other three were low thinning with different intensities: light (C), moderate (D) and heavy (E) thinnings. In this work, effects of these treatments on stand yield, mean tree and stand structure are studied. Results showed that with the heaviest thinning the total yield of the stand was a bit lower than in control treatment. This lost in production was imperceptible at early ages, so heavy thinning should be applied when stand is still young. According to these results the heaviest treatment of the trial is near the lower density limit for this species (critical basal area of Assmann). On the other hand, mean tree and stand structure characteristics became more suitable for increasing stand stability when thinning were heavy. The grater the intensity of thinning, the lesser the h/d ratio and the larger the square mean diameter. Moreover, more dominated and dying trees are removed. As conclusion we recommend low heavy thinning in early ages, reducing the intensity with age. Specially in stands of middle and high quality, the first thinning should be early, for instance at 20-25 years.